86.1k views
4 votes
Simplify the sum please help and show work

Simplify the sum please help and show work-example-1
User Jian Huang
by
5.4k points

1 Answer

4 votes

Factoring the second term shows you what the common denominator must be. Then multiply the first term by the appropriate version of 1 and add.


\displaystyle(4)/(m+9)+(5)/(m^2-81)=(4)/(m+9)+(5)/((m+9)(m-9))\\\\=(4(m-9))/((m+9)(m-9))+(5)/((m+9)(m-9))=(4(m-9)+5)/((m+9)(m-9))\\\\=(4m-36+5)/((m+9)(m-9))\\\\=(4m-31)/((m+9)(m-9))

User Teilmann
by
5.0k points